The existence of betutu for supporting culinary tourism in Gianyar Bali - Made Suardani; Luh Linna Sagitarini; Ida Ayu Kade Werdika Damayanti (Journal of Applied Sciences in Travel and Hospitality, 2021)
Gianyar Regency has local specialties menus such as Babi Guling, Bebek Betutu, Lawar, etc. However, betutu is the most menus ordered because it is halal menu which has its uniqueness, taste, and aromatic. Meanwhile, nowadays there are several culinary products which are seeked by guest such as KFC, Ayam Geprek, and chicken or duck roasted. It is needed to figure out whether betutu still exist or not and how can betutu still exist among society. This study was aimed to figure out whether betutu still exist or not and how to maintance betutu in order to support culinary tourism in Gianyar Regency. This study was qualitative research which used deep interview for collecting the data from the informants. For the result, it was revealed that betutu still exist among the tourists and local society. It was proven by the result of interview with six informants who revealed that 5 of them can produce more than 50 portion of betutu daily. They also gave positive response toward the questions given by the researchers that revealed betutu is still sought-after by the tourists. The betutu is still made by using the original recipes and served in traditional presentation. Not only tourists, betutu still exist among local society because betutu is used as a means in Hindu ceremonies.